The Digitalization Initiatives and Customer Satisfaction in the Logistics Management in the Philippines: Basis for an Action Plan - Lapitan, Maricar B. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examined the impact of digitalization initiatives—specifically automation, real-time tracking, and data-driven decision-making—on customer satisfaction in the Philippine logistics industry. Using a descriptive-correlational design with data from 101 respondents, the research found that all digitalization initiatives significantly influenced customer satisfaction, with automation and real-tracking being the most effective in improving visibility, reducing delays, and building trust. The strong positive correlation between digitalization and satisfaction highlights the strategic importance of technology in enhancing service quality. The study provides actionable recommendations for logistics firms to strengthen digital systems and adopt customer-focused strategies to remain competitive.